Determinants of consumer's intention towards adopting biometric authentication in electronic banking / Nur Najatul Najwa Suhaimi - Suhaimi, Nur Najatul Najwa (Faculty of Business Management, 2018)
The issue arises in term of the security of the electronic banking itself. The application of Internet Banking and ATM (Automated Teller Machine) indeed give great concern in security of the transactions to the consumers since both applications are widely used nowadays. The current authentication security system seems lacking and vulnerable to fraud and scam activities. There is an urgent need for innovation and technology enhancement for better security in electronic banking. Thus, the adoption of Biometric authentication system to strengthen the current security system is widely being proposed. This research aim is to study the factors of consumers' intention to adopt Biometric authentication in electronic banking. It specifically studies on electronic banking users of Universiti Teknologi Malaysia as the representative of the Skudai population. This research is based on data obtained from survey questionnaire that polled public expectation regarding on the Biometric Banking. The data was analysed to evaluate and examine the determinants and its level of influence towards the consumers' intention to use Biometric authentication system in electronic banking (ITA). The research suggested that the intention behaviours (ITA) are linked to the perception of biometric banking security (PBS), perceived usefulness (PU), perceived ease of use (PEU) and attitude to biometric banking use (ABU). The finding of this research shows that all the variables tested is significant with Consumers' Intention to Adopt Biometric Authentication (ITA). It is hope that the study can contribute to the improvement of the authentication security system in electronic banking in Malaysia.